Análise técnica: um estudo empírico à luz das finanças comportamentais - Medeiros, Augusto Santana Veras de (2009)
This work deepens the discussion in the Technical Analysis field, aligning it premises to the theoretical framework of Behavioral Finance. In this purpose, this paper aimed to make, for the period between the years of 2007 and 2008, an empirical study of the brazilian stock market in the light of Technical Analysis and Behavioral Finance, as well as verifying the performance of technical index as auxiliary instrument for the decision taking. This way, the work is divided in two parts. In the first part, adopting the complementarity hypothesis of behavioral-technique approach in the process of analysis and taking of decision in the stock market, is aimed to establish a relation between Technical Analysis (Dow Theory and Elliott Waves Theory) and Behavioral Finance assumptions in the interpretation of the subprime crisis in the Brazilian stock market, through a documentary research with referring information of the years 2007 and 2008, crisis development period. The results had evidenced the utility of these theories, not only for the analysis of the subprime crisis consequences, as, also, for the examination of financial market agent s behavior in a historical perspective of larger reach. In the second part, adopting the hypothesis that the technical index are capable to assist the investors in the process of decision taking, had been refined the performances of the Exponential Moving Average, Moving Average Convergence/Divergence, Relative Force Index, Stochastic and Directional System, using as base, Brazilian s stock market data referring to the year of 2007. The research results demonstrated that the Assertiveness (A) of the purchase signals is superior to the Assertiveness (A) of the sales signals the results had demonstrated as well, the uselessness of Directional System (DS) as beeper of the market s predominant trend.